REALISASI PENGELOLAAN ALOKASI DANA DESA (ADD) OLEH PEMERINTAHAN DESA NARUWOLO KECAMATAN JEREBUU KABUPATEN NGADA PADA TAHUN 2017-2021 - Due, Marta; Thalib, Sabra B. Wahab (Jurnal Riset Ilmu Akuntansi, 2022)
The purpose of study is to determine the realization of the Management Of Village allocation by the Government of Naruwolo Village, Jerebuu sb-district, Ngada district in 2017-2021. The research method used in this study is descriptive qualitative. The results of this study indicate that realization of village fund allocation management by the Naruwolo village Government starts from the planning stage,implementation, administration stage, accountanbility stages there are several obstacles in managing village fund allocation, namely the community does not understand the activities carried out by the Naruwolo Village government, there is a lot of work in the Naruwolo Village, so that there are mistake in reporting delays in village development activities. The efforts made by the Naruwolo village government in overcoming obstacles are conducting socialization with the Naruwolo village community and adjusting laws and regulations.